Budaya Organisasi Terhadap Kepuasan Kerja Pegawai Dimediasi Motivasi - Duha, Timotius; Dakhi, Yohanes (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
Research aims: This study investigates the effect of organizational culture on job satisfaction, which is mediated by motivation. Design/ Method/ Approach: The data is analyzed with path analysis through Partial Least Square and processed with Smart PLS software. Research Findings: The results of the study show that organizational culture and motivation have a positive effect on job satisfaction, Theoretical Contribution/ Originality: This research enriches the understanding that awareness of organizational culture can increase the willingness to behave voluntarily in the workplace, generating motivation and job satisfaction. Although motivation is not the only cause of job satisfaction, when budget constraints reduce employee income, motivation is the most important factor and quickly results in job satisfaction. Practical Implications: Organizational culture is applied to help work processes and achieve organizational targets. Strong synergy between employees needs to be used as a force to produce job satisfaction, even though they are in a situation of limited budgets Research Limitations: The limitation of this research is only one mediating variable, the variable of motivation